Pengaruh Pendapatan Asli Daerah (PAD) dan Karakteristik Pemerintah Daerah terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten/Kota Propinsi Papua - Mercy Irene Christine Siregar (STIM LASHARAN JAYA MAKASSAR, 2020)
This study aims (1) to identify and analyze the definition of corruption, (2) to identify and analyze the causes of corruption, (3) to the impact of corruption, (4) to prevent and eradicate corruption. The benefits of research are (1) the theoretical use of developing and expressing objectively in overcoming existing problems, especially those related to aspects of corruption, (2) providing insight into information for the public, law enforcement agencies and other parties on the performance of the local government of the regency / city of Jayapura.